PENERAPAN PEMBERIAN PIJAT PUNGGUNG TERHADAP SKOR KECEMASAN PASIEN GAGAL JANTUNG DI RSUD K.R.M.T. WONGSONEGORO KOTA SEMARANG - Ainnur Rahmanti; Rani Noor Maheda (Jurnal Kesehatan Medika Udayana, 2019)
Heart failure has an impact not only on one's physical condition but also on the psychological impact of anxiety. Patients with heart disease who experience psychosocial problems, especially anxiety, will have a slower recovery process and more severe physical symptoms they experience. Thus, an intervention is needed to provide back massage to overcome anxiety. The purpose of this study was to describe the application of back massage towards anxiety scores in heart failure patients.This study belongs to descriptive research using the case study approach method. The sample in this study were 2 subjects who suffered classification II and III heart failure according to NYHA who experienced low to moderate anxiety. Both subjects were given back massage therapy. Hamilton Anxiety Rating Scale (HARS) was used as the instrument to measure the level of anxiety. The results showed that there was a significant decrease in the two subjects who initially fell into the anxiety category into the category of low anxiety after being given back massage therapy for 15 minutes at 24-hour intervals for 3 days. In conclusion, back massage is recommended to be applied in the hospital as a nursing intervention to overcome anxiety in heart failure patients.